MALARIA IN CHILDREN: STUDY OF 160 CASES AT A PRIVATE CLINIC IN MANSEHRA - din, Jalal -ud-; Khan, Shamsher Ali; Ally, Sirajuddin Hassan (Journal of Ayub Medical College Abbottabad, 2006)
Background: This Study was conducted in a private clinic to report frequency, presentation and management of malaria in children presenting with fever. Methods: 160 Children of age varying from 42 days to 15 years were included in this study, during a period of 1999-2004. Results & Conclusions: Malaria was confirmed in 154 cases, including 114 male and 46 female children. In 6 cases malarial parasite was not seen on microscopic examination of their blood films. 142 cases were found to be suffering from vivax and 12 were suffering from falciparum malaria. Most of the cases were treated with amodiaquine and some of them were treated with other antimalarial drugs. Keywords: Malaria, Children